INDIAN FEDERALISM – PROBLEMS AND PROSPECTS (International Journal of Food and Nutritional Sciences, 2022)
The article examines the recent trends and issues in Indian federalism. Thefederal system has become transformedly in the last seven decades—from beingdismissed as a full-fledged federal system to a widely acclaimed federal system in theworld.